Long-term stability of maxillary anterior alignment in non-extraction cases - Luiz Filiphe Gonçalves Canuto; Marcos Roberto de Freitas; Karina Maria Salvatore de Freitas; Rodrigo Hermont Cançado; Leniana Santos Neves (Dental Press Editora, 2013)
OBJECTIVE: The purpose of this retrospective study was to evaluate long-term stability of maxillary incisors alignment in cases submitted to non-extraction orthodontic treatment. METHODS: The sample comprised 23 patients (13 female; 10 male) at a mean initial age of 13.36 years (SD = 1.81 years), treated with fixed appliances. Dental cast measurements were obtained at three different time points (T1 - pretreatment, T2 - posttreatment and T3 - long-term posttreatment). Variables assessed in maxillary arch were Little Irregularity Index, intercanine, interpremolar and intermolar widths, arch length and perimeter. The statistical analysis was performed by one-way ANOVA and Tukey tests when necessary. Pearson' correlation coefficients were used to investigate possible associations between the evaluated variables. RESULTS: There was no significant change in most arch dimension measurements during and after treatment, however, during the long-term posttreatment period, it was observed a significant maxillary incisors crowding relapse. CONCLUSION: The maxillary incisors irregularity increased significantly (1.52 mm) during long-term posttreatment. None of the studied clinical factors demonstrated to be predictive of the maxillary crowding relapse.